A Non-destructive Radar Device for Detecting Additive Materials in Concrete - Quy, Vu Ngoc; Dao, Toan Thanh; Trung, Ho Thanh (Engineering, Technology & Applied Science Research, 2023)
The use of electronic devices based on electromagnetic waves is promising for inspecting additives in structural concrete. However, the existing commercial devices are high-cost and do not publicly provide circuit design information. To overcome this issue, this study designed a low-cost nondestructive testing device with a radar sensor, using an HB-100 radar sensor module to generate and receive the radar wave. A suitable bandpass filter was used to suppress electrical noise in the received signal, an Arduino board was used for signal processing, and the measured data were displayed on a computer. The output at the IF pin of the sensor module presents the Doppler frequency and absorbance of the target materials. The device was tested to detect additives inside the concrete. An additive material can be recognized by the fact that the obtained signal magnitudes are different with different additive materials. The findings in this study can contribute to making a low-cost nondestructive testing device based on radar technology for structural concrete inspection.